A design exploration of the contemporary anti-fashion paradox : taste, rebellion, and digital distortion : a thesis presented in partial fulfilment of the requirements for a Master in Design at Massey University, Wellington, New Zealand - Zhao, Ruohan (Massey University, 2026)
Fashion rebellion manifests differently in the age of mass information and algorithmic influence. This thesis examines the paradox of anti-fashion, exploring how digital platforms simultaneously enable personal expression while accelerating the commodification of rebellion within the fashion system. Drawing on fashion theory and cultural studies on status and taste, the research considers how constant social media exposure shapes taste, influences decision-making, and distorts self-image. The research aims to reveal that anti-fashion is not solely about avant-garde aesthetics, fashion rebellion and deconstruction, but also about the designer’s intention, authenticity, and resistance to external pressures like consumer expectations. The design component investigates these ideas through a metaphorical design language informed by the four stages of a caterpillar’s metamorphosis. Victorian mourning wear is also examined as a historical reference as a symbol for the ‘death’ of traditional anti-fashion and its rebirth within contemporary culture. Draping experiments, fabric manipulations, and print development translate the forms, colours, and textures of the caterpillar and mourning garments into material explorations that reflect transformation and adaptation in contemporary society. The final design outcome synthesizes research, material experimentation, and print development into two looks, each corresponding to one stage of the caterpillar’s lifecycle. These works articulate an alternative vision of anti-fashion which is rooted in cyclical transformation, creative intention, and the negotiation between individuality and systemic influence. The thesis demonstrates how anti-fashion can continue to function as a tool of self-expression and resistance, even in a culture where rebellion is rapidly absorbed, commodified, and normalized.
Copyright holders of copyrighted images may use the Take Down Request link below to request their removal.
Keywords: 330315 Textile and fashion design